2002
DOI: 10.1046/j.1365-2141.2002.03879.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐myeloma activity of natural killer lymphocytes

Abstract: Summary. Natural killer (NK) cells are assumed to contribute to a graft-versus-leukaemia effect. In vitro experiments have shown that many leukaemic cells are NK-cell sensitive. Nevertheless, no data concerning the influence of purified NK cells on malignant myeloma (MM) cells exist. We co-incubated NK cells with three different MM cell lines and fresh bone marrow samples of nine MM patients. The proportion of vital MM cells was determined before and after co-cultivation by a flow-cytometry-based assay. All MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 30 publications
8
84
0
Order By: Relevance
“…48 Recent studies revealed the capability of human DCs to promote NK cell proliferation, IFN-g-secretion and tumor-directed cytotoxicity. 15,49,50 Following our observation that slanDCs can also efficiently trigger NK cells 34,44 and previous reports demonstrating effective NK cell-mediated lysis of myeloma cells, 51,52 we determined whether bortezomib influences the capability of slanDCs to activate these innate effector cells. Therefore, bortezomib-pretreated DCs were cocultured with immunomagnetically purified autologous CD56 þ CD3À NK cells in the presence of LPS for 18 h. As demonstrated in Figure 5, bortezomib significantly reduced the ability of LPS-activated slanDCs to improve IFN-g production by NK cells.…”
Section: Impact Of Bortezomib On Blood Dendritic Cells C Straube Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…48 Recent studies revealed the capability of human DCs to promote NK cell proliferation, IFN-g-secretion and tumor-directed cytotoxicity. 15,49,50 Following our observation that slanDCs can also efficiently trigger NK cells 34,44 and previous reports demonstrating effective NK cell-mediated lysis of myeloma cells, 51,52 we determined whether bortezomib influences the capability of slanDCs to activate these innate effector cells. Therefore, bortezomib-pretreated DCs were cocultured with immunomagnetically purified autologous CD56 þ CD3À NK cells in the presence of LPS for 18 h. As demonstrated in Figure 5, bortezomib significantly reduced the ability of LPS-activated slanDCs to improve IFN-g production by NK cells.…”
Section: Impact Of Bortezomib On Blood Dendritic Cells C Straube Et Almentioning
confidence: 97%
“…Labeled target cells were plated as triplicates in round-bottomed 96-well plates at 5 Â 10 3 per well and incubated with NK cells at an effector (E)-to-target (T) cell ratio of 20:1. After 4 h, 51 Cr release was determined in a beta counter.…”
Section: Chromium Release Assaymentioning
confidence: 99%
“…[11][12][13][14][15] Allogeneic hematopoietic cell transplantation is controversial in MM and often associated with high mortality, due in part to increased rates and severity of graft-versus-host disease (GvHD). 16 However, increased survival was shown for MM patients undergoing HLA-matched sibling hematopoietic cell transplantation after initial autologous transplantation compared to patients receiving tandem autologous transplants.…”
Section: Introductionmentioning
confidence: 99%
“…MM is an incurable disease with a median survival of a few years, recently improved by the introduction of new antimyeloma chemotherapeutic agents such as bortezomib and thalidomide/lenalidomide, and by the wider use of transplant procedures (7)(8)(9), in which part of the curative potential of allografts is attributed to a graft-versus-tumor effect mediated by donor lymphocytes (10,11). In this regard, a number of evidences in myeloma patients strongly support the antitumor potential of NK cells in response to immunomodulatory drugs or following allogeneic stem cell transplantation (12)(13)(14), and several studies have shown that the engagement of the NKG2D and DNAX accessory molecule-1 (DNAM-1)-activating receptors plays an important role in the recognition and killing of MM cells by NK cells (15)(16)(17). Indeed, MM cells can express the NKG2D ligands MICA/B (15,18), different UL16-binding proteins, and the DNAM1-ligands poliovirus receptor (PVR; CD155) and nectin-2 (19,20).…”
mentioning
confidence: 99%